Disruptive activity in a regulated industry : the case of telecommunications - Curwen, Peter; Whalley, Jason; Vialle, Pierre (Emerald Publishing Limited, 2019)
Theoretical and empirical work examining disruptive activity within industry has previously been restricted to the free market, even if an element of ad hoc government interference has occurred. In contrast, this book makes a unique evaluation of a situation that prevails across a significant part of the industrial sector where involvement is subject to the acquisition of an operating licence. Taking telecommunications as an illustrative industry, with a particular focus on mobile telecommunications, the book focuses on the regulatory bodies that are tasked with licence issuance. New entry is usually attempted by a single company, often with existing links within the telecommunications sector, and usually within a single country. This book provides detailed accounts of both the individual countries and international operators in question, while also including a case study of CK Hutchinson which has been associated with multiple country entries. It also examines how disruptive activity is evolving from its roots in the mobile sector to encompass so-called "quad-play" which includes fixed-wire broadband and pay-TV.Disruptive Activity in a Regulated Industry: The Case of Telecommunications will appeal to postgraduate researchers and academics in the fields of economics, innovation, regulation, and governance.
Includes index.
Keywords: Telecommunication -- Technological innovations.; Disruptive technologies.; Business & Economics -- Industries -- General.; Business strategy.; elektronické knihy; electronic books